Penerapan Business Intelligence untuk Analisis Kinerja Sektor Pendidikan di Kota Yogyakarta - Lubis, Khadijah Chairunnisa; Nasution, Muhammad Irwan Padli (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to analyze the performance of the education sector in Yogyakarta City through the application of business intelligence. The primary method used is quantitative data analysis, with data collected from various sources, including surveys and official reports. The results indicate that the application of business intelligence can enhance the efficiency of education data management, provide better insights into student needs, and assist in strategic decision making by local government. Additionally, the use of interactive dashboards allows stakeholders to monitor education performance in real-time. The conclusion of this research emphasizes that business intelligence is an effective tool for improving the performance of the education sector in Yogyakarta City.